Memperkokoh Pendidikan Karakter Melalui Pembelajaran Sirah Terpadu di SMP Al Hikmah Surabaya - Yiyin Isgandi (Proceedings of Annual Conference for Muslim Scholars, 2017)
Abstract: The character education is an inovation to reach the goal of national education. The issue of morals decadence and lackness of nationalist soul made that goal still far from our hope. So far, the implementation of character values has only implemented as the integrated subtance at every lesson, it only concern at the cognitive assesment. The inovation of integrated teaching of Sirah at Junior Hight School of Al Hikmah Surabaya can strengthen the character education. Data has taken from primare resourses of lesson books of Sirah, observation and interview with managers of school, teachers of Sirah, and students. It has been analyzed using descripted qualitative approach. The results of this qualitative research shows that the integrated teaching of Sirah can strengthen character education of the students in the school, both internally and externally. Through method of modelling and Contextual Teaching Learning (CTL), students can implement four main values of character; honest, smart, strong, and care in their daily life.Keywords: The Character Education, Character, Integrated Teaching, Sir’ah